Technology applied to optimise training for improvement of front-crawl swimming performance - Toussaint, H. M. (Biomechanics and Medicine in Swimming X, 2006)
Peak performances in sport require the full deployment of all powers an athlete possesses. The development of those powers require years of hard training. It may be argued that training-time will be especially efficient when devoted to the enhancement of those performance factors that are weak links in the individual performance chain. Developments of measurement technology (with special reference to the MAD-system) have aided the sport scientist in identifying several factors as determinants of performance. These include drag, propulsion technique, and mechanical power (2). The development of this knowledge provides the modern coach with some guide-lines how to design training programmes. However, it may be argued that training-time will be especially efficient when devoted to the enhancement of those performance factors that are weak links in the individual performance chain. This implies that on an individual level it is necessary to identify in what phase of the process the performance system first becomes insufficient. Those factors when improved would immediately contribute to overall performance and, consequently, training time allotted to these factors would be well spent. In the training process it is rather challenging for coaches to determine which training load is sufficient to induce the required adaptation without risk of overtraining. More insight in the individual relation between training dose and adaptation response is necessary to optimise this training process. Training dose and changes in performance capacity can be modelled (1). In this model performance is a systems output varying over time according to the systems input; the training dose or training impulse (TRIMP), quantified from exercise intensity and volume. The subject is represented by a system with a daily amount of training as input and performance capacity as output. It is possible to use heart rate recordings as indicator for the training dose while simple time trials can be used to monitor the development of the performance capacity (see Figure 1). A sketch will be given how technological developments leading to instrumented swimming wear could be put to use to optimise the training process.